Strategic e-leadership skills – the Le@d3.0 Academy case - Barroca, Ana; Neto, Catarina (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Strategic e-leadership skills are that peculiar blend of social and technological skills that a manager needs in order to be truly effective in the current labour landscape. Skills such as decision making, giving feedbacks to your team, empowering creativity (some of the so called ‘soft e-skills’) are very important in the current labour market. On the other hand, also having a basic digital literacy or knowing the base of coding (or ‘hard e-skills’, the more technical ones) are essential to achieve business goals in the Digital Age. The Le@d3.0 Academy project aims to establish a long lasting Knowledge Alliance between academy and industry. This will be done through the online support for strategic e-leadership skills training based on OERs (Open Educational Resources). The research phase allowed the project consortium to identify the 6 main clusters of skills required by trainers, managers and students and, consequently, to develop a solid scientific and operational foundation for future project operations. Designing the approaches for the learning process embedded in the online platform was the next challenge that the consortium had to overcome. Starting from a perspective that focuses upon the specific needs, values and entry levels of the target groups, how a digital environment can effectively support and engage users throughout a free flow process that makes them responsible of their own development?